Heterogeneity in habitat and microclimate delay butterfly community tracking of climate change over an elevation gradient - Álvarez, Hugo Alejandro (2024)
Gradients in community diversity and composition rarely track rates of warming, prompting efforts to understand the factors causing non-equilibrium responses to climatic change and their implications for conservation. Here, we test the roles of fine-resolution habitat heterogeneity and microclimate in delaying butterfly community responses to warming over a mountain elevation gradient. We assess species diversity and Community Temperature Index (CTI) in 2004–2005 and 2017 across 120 transect sites in the Sierra de Guadarrama (Spain), modelling temperatures based on topography, and vegetation structure based on LiDAR. A humped elevation gradient in species diversity was maintained over time. However, diversity in the later period was more positively related to vegetation heterogeneity, and sites with reduced rates of warming and greater forest cover maintained or increased their diversity. Site CTI declines with increasing elevation, showing little evidence of systematic change over the gradient between periods, although CTI increased most in locations with the greatest rates of spring microclimatic warming. Our results show that delays in community tracking of climatic conditions could result partly from positive effects of habitat and topographic heterogeneity providing microclimatic buffering against warming to existing communities; although barriers to colonization could also delay diversity increases and community thermophilization at high elevations. We suggest that protecting and managing complex habitats with high community diversity, and identifying localized microclimates that buffer populations against negative effects of warming, are more immediate conservation priorities over elevation gradients than efforts to ensure that communities track prevailing rates of warming.